Eremomycin pyrrolidide: a novel semisynthetic glycopeptide with improved chemotherapeutic properties - Olsufyeva EN; Shchekotikhin AE; Bychkova EN; Pereverzeva ER; Treshalin ID; Mirchink EP; Isakova EB; Chernobrovkin MG; Kozlov RS; Dekhnich AV; Preobrazhenskaya MN (Dove Medical Press, 2018)
Evgenia N Olsufyeva,1 Andrey E Shchekotikhin,1,2 Elena N Bychkova,1 Eleonora R Pereverzeva,1 Ivan D Treshalin,1 Elena P Mirchink,1 Elena B Isakova,1 Mikhail G Chernobrovkin,3 Roman S Kozlov,4 Andrey V Dekhnich,4 Maria N Preobrazhenskaya1,† 1Gause Institute of New Antibiotics, Moscow, Russia; 2Mendeleyev University of Chemical Technology, Moscow, Russia; 3Drugs Technology, Khimki, Russia; 4Institute of Antimicrobial Chemotherapy, Smolensk State Medical University, Smolensk, Russia †This author passed away on December 25, 2014 Purpose: Development of new semisynthetic glycopeptides with improved antibacterial efficacy and reduced pseudoallergic reactions.Methods: Semisynthetic glycopeptides 3–6 were synthesized from vancomycin (1) or eremomycin (2) by the condensation with pyrrolidine or piperidine. The minimum inhibitory concentration (MIC) for the new derivatives was measured by the broth micro-dilution method on a panel of clinical isolates of Staphylococcus and Enterococcus. Acute toxicity (50% lethal dose, maximum tolerated doses), antibacterial efficacy on model of systemic bacterial infection with S. aureus and pseudoallergic inflammatory reaction (on concanavalin A) of eremomycin pyrrolidide (5) were evaluated in mice according to standard procedures.Results: The eremomycin pyrrolidide (5) was the most active compound and showed a high activity against Gram-positive bacteria: vancomycin-susceptible staphylococci and enterococci (minimum inhibitory concentrations [MICs] 0.13–0.25 mg/L), as well as vancomycin-intermediate resistant Staphylococcus aureus (MICs 1 mg/L). Antimicrobial susceptibility tested on a panel of 676 isolates showed that 5 had similar activity for the genera Staphylococcus and Enterococcus with MIC90=0.5 mg/L, while vancomycin had MIC90=1–2 mg/L. The number of resistant strains of Enterococcus faecium (vancomycin-resistant enterococci) (MIC =64 mg/L) with this value was 7 (8%) for vancomycin (1) and 0 for the compound 5. In vivo comparative studies in a mouse model of systemic bacterial infection with S. aureus demonstrated that the efficacy of 5 was notably higher than that of the original antibiotics 1 and 2. In contrast to 1, compound 5 did not induce pseudoallergic inflammatory reaction (on concanavalin A).Conclusion: The new semisynthetic derivative eremomycin pyrrolidide (5) has high activity against staphylococci and enterococci including vancomycin-resistant strains. Compound 5 has a higher efficacy in a model of staphylococcal sepsis than vancomycin (1) or eremomycin (2). In striking contrast to natural antibiotics, the novel derivative 5 does not induce a pseudoallergic inflammatory reaction to concanavalin A and therefore has no histamine release activity. These results indicate the advantages of a new semisynthetic glycopeptide antibiotic eremomycin pyrrolidide (5) which may be a prospective antimicrobial agent for further pre-clinical and clinical evaluations. Keywords: semisynthetic glycopeptides, antibacterial activity, pseudoallergic reaction, antibacterial efficacy